The Language Medium Policies: A Study on the Development of Independent Chinese Secondary Schools (ICSS) in Malaysia - Wong, Vivien (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
This paper aims to examine the implementation of the language medium policy and its relative impact on the development of Malaysian Chinese Secondary Schools. The education pathway of the Chinese community in Malaysia is unique, where most of them attain primary education through Chinese-medium schools, but would face a dilemma when deciding on their secondary education pathway. The drastic change of education policy in the early 1960s, coupled with the rising dominance of the National language has marginalised the development of Chinese secondary education and later separated the Chinese secondary schools. This article suggests that the language medium policy is perceived as dysfunctional, as it had failed to result in unity through the implementation of a National language policy, along with strong resistance by the Malaysian Chinese community. This can be seen through the development of the Independent Chinese Secondary Schools (ICSS), which segregated national education into disparate systems. It is also closely linked to the question of access to education opportunities and the Malaysian Chinese preference for the Chinese language as their medium of instruction that contributed to the development and sustainability of the ICSS in Malaysia.